Perancangan Aplikasi Berbasis Web untuk Penentuan Penjual di PT Bahtera Multi Cemerlang dengan Algoritma TOPSIS - Allvi, Reyner; Bororing, Grace Martha Geertruida (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The rapid development of information and communication opens up quite a lot of opportunities in the business world, where one example is making decisions in the form of information quickly, precisely, and accurately. Thus, decision-making becomes an important fulcrum that we want to take a step. TOPSIS is a method based on the Multi Criteria Decision Making (MCDM) optimization tool. Where, TOPSIS is designed to solve the problem of choosing a middle way or achieving a solution. Where, TOPSIS reaches a decision based on the calculation of determining the distance for the best solution and the worst solution. (Khan & Maity, 2017) This research was conducted qualitatively, using the Personal Extreme Programming method. The advantage of Personal Extreme Programming, the modules created can be changed quickly. And Personal Extreme Programming does not require many programmers in the team. The results of this study are to provide a method or way to facilitate the entry of progress data that has been carried out by PT. Multi Bahtera Cemerlang. Then make it easier for decisions to be made. With the aim of increasing work efficiency in the company PT. Multi Bahtera Cemerlang. This research will produce a website in the form of web progress and web decision selection using the TOPSIS Algorithm. Then, the work process in the company PT. Multi Bahtera Cemerlang is faster. As well as applications that is made can be used easily.